Long-distance renewable hydrogen transmission via cables and pipelines - Miao, Bin (2022)
Intermittency is one of the main obstacles that inhibit the wide adoption of the renewable energy in the power sector. Small-scale fluctuations can be tackled by short-term energy storage system, whereas long-term or seasonal intermittencies rely on large-scale energy management solutions. Besides the supply and demand mismatch in temporal domain, renewable energy sources are usually far away from consumption points. To connect the energy sources to the demand cost-effectively, cable transmission is usually the default option, and considering the long distance, other emerging energy carriers such as hydrogen could be a feasible option. However, there is handful studies on the quantitative evaluation of the long-distance energy transmission cost. This paper investigated the economic feasibility of renewable energy transmission via routes of power cable and gas pipeline. In the direct power transmission case, renewable energy is transmitted via HVDC cable and then converted to hydrogen for convenient storage. The alternative case converts renewable energy into hydrogen at the source and transports the hydrogen in the gas pipeline to consumers. Existing data available from public domain are used for cost estimation. Results show that the improvements of capacity factor and transmission scale are the most cost-effective approach to make the renewable hydrogen economically viable. At 4000 km of transmission distance, renewable hydrogen LCOE of 7 US$/kg and 9 US$/kg are achievable for the corresponding optimum cases, respectively.